Programmed Cell Death Protein 1/Programmed Cell Death Ligand 1 Signaling Pathway Mediated Interleukin-10 and Bacterial Biofilm Formation to Drug Resistance Mechanism of Pneumoniae Meningitis: PD-1/PD-L1 signaling pathway in Pneumoniae Meningitis - Ma, Chen; Zhang, Yi; Lei, Jin’e; Zhang, Jing; Li, Fang; He, Xiaqin; Yuan, Jing; Li, Wen; Chen, Wei (Cellular and Molecular Biology, 2023)
It aimed to explore the resistance and biofilm formation characteristics of pneumococcal meningitis (PM) and the mechanism of programmed cell death protein 1/programmed cell death ligand 1 (PD-1/PD-L1) signaling pathway (SPW). Firstly, the drug susceptibility test of 32 Streptococcus pneumoniae strains isolated from patients with PM and the biofilm semi-quantitative determination was performed. Then, the PM mouse model was constructed. The differences in brain morphology, blood-brain barrier (BBB) permeability, water content, cytokines such as interferon-γ (IFN-γ), interleukin-10 (IL-10), and chemokine C-X-C ligand 10 (CXCL10), and levels of PD-1 and PD-L1 in the normal control (NC), sham operation, PM, and PD-1 antibody (PM + PD-1 Ab)groups were compared and analyzed. The results showed that streptococcus pneumoniae had multidrug resistance, and the thickness of biofilm decreased with the increase of penicillin minimum inhibitory concentration (MIC). Compared with the NC and Sham groups, BBB permeability, water content, levels of IFN-γ and IL-10, and PD-1 and PD-L1 were signally increased in the PM and PM + PD-1 Ab groups, while CXCL10 level was decreased, exhibiting differences withP<0.05. Based on the PM group, BBB permeability, water content, levels of IFN-γ and CXCL10, and PD-1 and PD-L1 were remarkably decreased in the PM + PD-1 Ab group, while the IL-10 level was observably increased (P<0.05). Therefore, high-MIC penicillin could inhibit the thickness of Streptococcus pneumoniae biofilm, while blocking the PD-1/PD-L1 pathway exerted an improving effect on the PM symptoms.